Disinfestation of Sitophilus zeamais Motschulsky in stored maize using microwave - Ravipat Lapcharoensuk; Sattawat Wisetsri; Supattra Meesuk (My University, 2020)
This study aimed primarily to investigate on disinfestation of maize weevil (Sitophilus zeamais Motschulsky) in maize storage by using microwave method. Specimens of Maize weevils were cultured for 30 days in a maize sample with 17% moisture content (wet basis). Several different life stages of the maize weevil (egg, young larva, old larva, pupa and adult) were then infested in the sample. Next, the maize sample was exposed to 200, 300 and 450 W of microwave power for 60, 120 and 180 s, and the number of weevils were counted after each treatment. Moreover, the sample was kept for another 2 months to see whether the eggs have survived the treatment and grown to be adults. In addition, the effects of the level of microwave power and exposure time on the property of the maize sample were observed. The quality parameters investigated were moisture content, colour and protein and fat contents. It was found that, at 300 W of power for 180 s, the microwave was able to disinfect weevils at all life stages successfully, while the quality of the maize sample did not change significantly at the tested microwave settings and exposure times, except for the protein content. These findings indicate that microwave can be a good alternative to harmful chemical methods for disinfestation of maize weevils.
Keywords: Maize weevil; Rice weevil; Insect Pest Control Strategies